Antidrug antibodies in psoriasis: a systematic review4. (February 2014) - Hsu, L.; Snodgrass, B.T.; Armstrong, A.W.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Antidrug antibodies have been shown to form in patients with psoriasis receiving infliximab, etanercept, adalimumab or ustekinumab. Certain antidrug antibodies have been noted to influence treatment efficacy. What does this study add? This is among the first reviews to examine the available scientific evidence on the prevalence of antidrug antibodies against biological agents, their impact on treatment efficacy, and the utility of concomitant methotrexate to prevent antidrug antibody formation in patients with psoriasis.